The Blockade of Transmembrane Cl- Flux Mitigates I/R-Induced Heart Injury via the Inhibition of Calpain Activity - Jian-Ying Zhang; Feng Wu; Xiao-Ming Gu; Zhen-Xiao Jin; Ling-Heng Kong; Yuan Zhang; Jing-Jun Zhou; Feng Gao (Cellular Physiology and Biochemistry, 2015)
Aims: The aim of this study was to determine whether calpain is involved in Cl- -induced myocardial ischemia/reperfusion (I/R) injury. Methods: Isolated rat hearts were subjected to either 45 min of global no-flow ischemia followed by reperfusion or successive perfusion with Ca2+ -free KH solution for 3 min and normal KH solution for 30 min, also known as Ca2+ paradox. Results: The hearts in the I/R group exhibited increases in myocardial injury area, LDH release, caspase 3 activity and apoptotic indices and a marked decline in cardiac performance. As was the case regarding the effects of MDL 28170, an inhibitor of calpain, treatment with 5 µM NPPB, 5 µM DIDS and low Cl- significantly attenuated cardiac injury. Moreover, each of the treatments significantly protected against Ca2+ overload-induced injury in the setting of Ca2+ paradox. The Western blot and immunofluorescence data revealed that there was an increase in the percentages of calpain membrane-positive cells and the numbers of fragments resulting from the calpain-mediated proteolysis of α-fodrin in both the I/R and the Ca2+ paradox, indicating that the activation of calpain occurred. More importantly, these effects were mitigated by the blockade of transmembrane Cl- flux, as was accomplished via MDL 28170. Conclusion: Our results provide evidence that the blockade of transmembrane Cl- flux mitigates I/R-induced cardiac injury via the inhibition of calpain activity. They also indicate that intracellular Ca2+ overload regulates calpain activation in the setting of Cl- -induced injury.